Primary, secondary, and tertiary amines for CO2 capture: Designing for mesoporous CO2 adsorbents - Ko, Young Gun; Shin, Seung Su; Choi, Ung Su (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2011)
CO2 emissions, from fossil-fuel-burning power plants, the breathing, etc., influence the global worming on large scale and the man's work efficiency on small scale. The reversible capture of CO2 is a prominent feature of CO2 organic-inorganic hybrid adsorbent to sequester CO2. Herein, (3-aminopropyl) trimethoxysilane (APTMS), [3-(methylamino)propyl] trimethoxysilane (MAPTMS), and [3-(diethylamino) propyl] trimethoxysilane (DEAPTMS) are immobilized on highly ordered mesoporous silicas (SBA-15) to catch CO2 as primary, secondary, and tertiary aminosilica adsorbents. X-ray photoelectron spectroscopy was used to analyze the immobilized APTMS, MAPTMS, and DEAPTMS on the SBA-15. We report an interesting discovery that the CO2 adsorption and desorption on the adsorbent depend on the amine type of the aminosilica adsorbent. The adsorbed CO2 was easily desorbed from the adsorbent with the low energy consumption in the order of tertiary, secondary, and primary amino-adsorbents while the adsorption amount and the bonding-affinity increased in the reverse order. The effectiveness of amino-functionalized (1 degrees, 2 degrees, and 3 degrees amines) SBA-15s as a CO2 capturing agent was investigated in terms of adsorption capacity. adsorption-desorption kinetics, and thermodynamics. This work demonstrates apt amine types to catch CO2 and regenerate the adsorbent, which may open new avenues to designing "CO2 basket". (C) 2011 Published by Elsevier Inc.